Time consuming and cost price of dental treatment and prevention at the present stage - A. E. Olesov; A. I. Melnikov; V. N. Olesova; E. E. Nikonchuk; A. V. Lesnyak; L. A. Skorikova (Кубанский научный медицинский вестник, 2014)
Based on the timing, material costs, depreciation of equipment, as well as the wages of doctors and nurses in accordance with the Presidential Decree of 7.05.2012 № 597 «On measures for implementation of the state social policy» calculated cost price of modern methods of treatment and prevention of dental diseases.